2019
DOI: 10.1186/s13104-019-4365-2
|View full text |Cite|
|
Sign up to set email alerts
|

Role of empathy in the perception of medical errors in patient encounters: a preliminary study

Abstract: Objective Healthcare professionals’ empathy have been empirically demonstrated to decrease the risk of medical errors. Medical errors affect patient’s outcomes and healthcare providers’ well-being. Therefore, the purpose of this study was to determine the relationship between patients’ perception of healthcare providers’ empathy, their intention to adhere to treatment, and their perception of medical errors made. An anonymous survey was emailed to staff at a health center and an urban university i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Improved decision-making and judgement coupled with reductions in stress, anxiety, and distress may aid providers in emergency scenarios by allowing them to focus on making accurate diagnoses and treatment plans, but also reduce outstanding anxiety and rate of errors (Hannan et al, 2019; Panagioti et al, 2018). With less errors, healthcare trainees may experience less emotional exhaustion and greater personal accomplishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved decision-making and judgement coupled with reductions in stress, anxiety, and distress may aid providers in emergency scenarios by allowing them to focus on making accurate diagnoses and treatment plans, but also reduce outstanding anxiety and rate of errors (Hannan et al, 2019; Panagioti et al, 2018). With less errors, healthcare trainees may experience less emotional exhaustion and greater personal accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…With a large amount of the American population engaged in action or shooter type gameplay, possible concerns pertaining to empathy may arise (e.g., Anderson et al, 2010; Bavelier et al, 2011; Calvert et al, 2017; Gentile et al, 2014; Lei et al, 2019). Concerns surrounding empathy in gamers are particularly important for healthcare providers participating in gaming as empathy influences treatment outcomes, patient satisfaction, rate of medical errors, patient and staff wellbeing, and trust (Hannan et al, 2019; Panagioti et al, 2018; Sterkenburg & Vacaru, 2018). Physician burnout, specifically, has been tied to decreased empathy and increased personal distress, which can be a result of by emotional exhaustion, low satisfaction, lack of achievement, and depersonalization (e.g., Sterkenburg & Vacaru, 2018; Tei et al, 2014; von Harscher et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Patient-centered care is initiated by various empathic healthcare practitioners. A significant correlation between physicians' empathy towards patients improved patients' adherence to medication, increased satisfaction, and positive treatment outcomes have been well developed (Hannan et al, 2019). Duarte, Pinto-Gouveia and Cruz (2016) defined empathy as "the ability of an individual to consider others᾿ feelings" (p.2).…”
Section: Introductionmentioning
confidence: 99%
“…33,38 -43 Association of American Medical Colleges’ Physician Competency Reference Set identifies Interpersonal and Communication Skills as another core aspect of care, stressing that physicians should “demonstrate sensitivity, honesty, and compassion in difficult conversations” as well as “insight and understanding about emotions and human responses to emotions.” 44 These are skills of empathy, or the “cognitive attribute that involves an ability to understand the patient’s inner experiences and perspective.” 45 Positive outcomes of physician empathy and patient-centered care as described by patients include greater satisfaction, 46 -48 consistent treatment adherence, 47 decreased anxiety, 49 and the perception of fewer medical errors. 50 While some research has found nonsignificant or positive change throughout medical school, 51,52 other studies found a decrease in empathy throughout medical school and residency, particularly during the third year. 53,54…”
Section: Introductionmentioning
confidence: 99%
“…45 Positive outcomes of physician empathy and patient-centered care as described by patients include greater satisfaction, [46][47][48] consistent treatment adherence, 47 decreased anxiety, 49 and the perception of fewer medical errors. 50 While some research has found nonsignificant or positive change throughout medical school, 51,52 other studies found a decrease in empathy throughout medical school and residency, particularly during the third year. 53,54 The aim of this study is to compare medical student perception of EOL care goals to those of hospice patients.…”
Section: Introductionmentioning
confidence: 99%